2014
DOI: 10.1007/s11746-014-2488-0
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Biodiesel Feedstock Using GCMS and Unsupervised Chemometric Methods

Abstract: Various biodiesel feedstocks were evaluated using gas chromatography-mass spectrometry data combined with unsupervised chemometric methods of analysis. Peak areas of the fatty acid methyl esters (FAMEs) present in the biodiesel feedstocks (soybean oil, canola oil, waste grease, animal tallow, etc.) were utilized. The importance of chromatographic parameters, such as temperature program and column polarity, was examined with respect to the clustering that was observed using principal component analysis (PCA) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…This analysis method can be used with little knowledge of chemometric and preprocessing methods and simple, user friendly chemometric software. Previous research in this area has shown that using peak areas rather than the entire chromatogram does not bias simple data sets [28]. Multifeedstock samples were treated in a similar way, with the six most abundant FAMEs in the mixture used.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This analysis method can be used with little knowledge of chemometric and preprocessing methods and simple, user friendly chemometric software. Previous research in this area has shown that using peak areas rather than the entire chromatogram does not bias simple data sets [28]. Multifeedstock samples were treated in a similar way, with the six most abundant FAMEs in the mixture used.…”
Section: Discussionmentioning
confidence: 99%
“…Previous work in our research laboratory has determined optimal separation conditions of several biodiesel feedstocks on three different GC column chemistries and utilized unsupervised chemometric methods to characterize feedstock type [27,28,29]. The current research expands previous research by employing separation and chemometric methods for biodiesel-diesel blends made from these same feedstocks and several diesel sources.…”
Section: Introductionmentioning
confidence: 86%
“…Although these methods are not directly related to parameters for evaluation of the quality of the biofuel, they are useful to classify the biodiesel based on the feedstock [142][143][144][145][146][147] or to check the biodiesel content and adulteration in diesel/biodiesel blends. Although these methods are not directly related to parameters for evaluation of the quality of the biofuel, they are useful to classify the biodiesel based on the feedstock [142][143][144][145][146][147] or to check the biodiesel content and adulteration in diesel/biodiesel blends.…”
Section: Infrared Spectrometrymentioning
confidence: 99%
“…For separations involving biodiesel-diesel blends, many analyzers want to determine feedstock type or concentration of biodiesel [4,18]. The identification of feedstock depends on the identity of the FAMEs present, often with large differences in components, but for some it can be minor differences in isomers [19]. Our lab has investigated the use of chemometric methods for the determination of feedstock and concentration using the full chromatogram as well as using peak areas of major biodiesel and diesel components [20,21].…”
Section: Introductionmentioning
confidence: 99%